La literatura en contextos de enseñanza-aprendizaje de español como L2 / Literature in Contexts of Teaching and Learning Spanish as Second Language - Asensio Pastor, Margarita Isabel (Revista Fuentes, 2016)
Este trabajo se plantea la literatura, no solo como un recurso más para una clase de español lengua extranjera (E/LE) o segunda lengua (L2), sino como materia obligatoria del currículo de alumnos extranjeros que se encuentran escolarizados en España, en concreto en la educación obligatoria – Educación Primaria y Educación Secundaria Obligatoria (ESO)-. Estos discentes habrán de enfrentarse a situaciones lingüísticas, sociolingüísticas y pragmáticas que no estarán solo relacionadas con la vida cotidiana como ir a un restaurante o comprar en una tienda, etc., sino que se encontrarán con situaciones de tipo más académico como es, precisamente, el estudio de la literatura. Abstract In schools, the study of a second language in immersion contexts raises a broader horizon for migrant students than the functional learning of the language. Among the subjects that immersion students have to study we find Spanish language and literature. The contributions of the latter, from a communicative point of view, encourage the development of both the communicative and literary competence of students. This results in a more successful integration process in the target community. In this way, this article looks at the subject of Spanish Language and Literature in Compulsory Education within the specific context of migrant students. It also studies the role played by literature in the teaching of foreign and second languages, and the contributions of the communicative approaches in the achievement and improvement of these students’ communicative competence. This article ends with a reflection on the values of literary education.